Force evaluation of tendon routing for underactuated grasping - Clark,AB; Liow,L; Rojas,N (Journal of Mechanical Design, 2021)
While the modeling analysis of the kinetostatic behavior of underactuated tendon-driven robotic fingers has been largely addressed in the literature, tendon routing is often not considered by these theoretical models. The tendon routing path plays a fundamental role in defining joint torques, and subsequently, the force vectors produced by the phalanges. However, dynamic tendon behavior is difficult to predict and is influenced by many external factors including tendon friction, the shape of the grasped object, the initial pose of the fingers, and finger contact points. In this paper, we present an experimental comparison of the force performance of nine fingers, with different tendon routing configurations. We use the concept of force-isotropy, in which forces are equal and distributed on each phalanx as the optimum condition for an adaptive grasp. Our results show only some of the finger designs surveyed exhibited a partial adaptive behavior, showing distributed force for the proximal and distal phalanxes throughout grasping cycles, while other routings resulted in only a single phalanx remaining in contact with the object.